Orbital ebook A novel. - Harvey, Samantha (Atlantic Monthly Press, 2023)
WINNER OF THE BOOKER PRIZE 2024 • A NEW YORK TIMES BESTSELLER **New York Times Book Review February Book Club Pick** Winner of the 2024 Hawthornden Prize Shortlisted for the 2024 Orwell Prize for Political Fiction Shortlisted for the 2024 Ursula K. Le Guin Prize for Fiction One of Barack Obama's Favorite Books of 2024 A singular new novel from Betty Trask Prize-winner Samantha Harvey, Orbital is an eloquent meditation on space and life on our planet through the eyes of six astronauts circling the earth in 24 hours "Ravishingly beautiful." — Joshua Ferris, New York Times A slender novel of epic power and the winner of the Booker Prize 2024, Orbital deftly snapshots one day in the lives of six women and men traveling through space. Selected for one of the last space station missions of its kind before the program is dismantled, these astronauts and cosmonauts—from America, Russia, Italy, Britain, and Japan—have left their lives behind to travel at a speed of over seventeen thousand miles an hour as the earth reels below. We glimpse moments of their earthly lives through brief communications with family, their photos and talismans; we watch them whip up dehydrated meals, float in gravity-free sleep, and exercise in regimented routines to prevent atrophying muscles; we witness them form bonds that will stand between them and utter solitude. Most of all, we are with them as they behold and record their silent blue planet. Their experiences of sixteen sunrises and sunsets and the bright, blinking constellations of the galaxy are at once breathtakingly awesome and surprisingly intimate. Profound and contemplative, Orbital is a moving elegy to our environment and planet.